Ginkgolic Acid Protects against Aβ-Induced Synaptic Dysfunction in the Hippocampus - Mango, Dalila; Weisz, Filippo; Nisticò, Robert (Frontiers in Pharmacology, 2016)
Ginkgo leaf is the most used form of supplement for cognitive ailments. The standardized extract formulation EGb 761 is a dietary supplement with proven benefit in several neurological and psychiatric conditions including memory decline in Alzheimer’s disease, schizophrenia and dementia. Ginkgolic acid is a component of this extract which shows pleiotropic effects including antitumoral and anti-HIV action; however its effect on memory is still unknown. Here, we carried out an electrophysiological analysis to investigate the effects of ginkgolic acid on long term potentiation and synaptic transmission at CA1 hippocampal synapses. We also evaluated the potential rescuing effect of ginkgolic acid on the synaptic dysfunction following in vitro application of Aβ. Data obtained indicate that ginkgolic acid exerts neuroprotective effects against Aβ-induced impairment of neurotransmitter release and synaptic plasticity.